2015
DOI: 10.1590/s0104-40362015000400008
|View full text |Cite
|
Sign up to set email alerts
|

Políticas públicas para acesso de pessoas com deficiência ao ensino superior brasileiro: uma análise de indicadores educacionais

Abstract: ResumoO presente trabalho tem por objetivo analisar as políticas relativas às matrículas da educação especial no ensino superior brasileiro com base em indicadores educacionais. A pesquisa se caracteriza como descritivo-analítica com base documental, cujas fontes de dados foram resumos técnicos e planilhas do Censo da Educação Superior no período de 2000 a 2011 e documentos do Programa Incluir no período de 2005 a 2011, quinquênio em que foi implantado. A escolha pela década em questão justifica-se pelas ações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
1
3
0
4
Order By: Relevance
“…This means that the school must pay special attention to these critical moments: starting at the school, the transition between school years, cycles or stages; attention during and after periods of hospitalisation; or simply the day‐to‐day routine of these pupils. As in the study by Martins, Leite, and Lacerda (), the educational experiences recorded here still reveal barriers to implementing public policies.…”
Section: Discussionsupporting
confidence: 59%
“…This means that the school must pay special attention to these critical moments: starting at the school, the transition between school years, cycles or stages; attention during and after periods of hospitalisation; or simply the day‐to‐day routine of these pupils. As in the study by Martins, Leite, and Lacerda (), the educational experiences recorded here still reveal barriers to implementing public policies.…”
Section: Discussionsupporting
confidence: 59%
“…Many of the scientific papers used to discuss the results presented here refer to publications in the international literature, given the still restricted choice of studies conducted with university students with ASD in the national territory -although studies on this topic are already found. This is a piece of information to be highlighted, especially considering the growing number of students with ASD entering the country's universities due to public policies that encourage this initiative (Martins, Leite, & Lacerda, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…O primeiro deles, denominado "Acessibilidade: inclusão e permanência" tem como meta a ampliação do número de discentes, docentes e técnicos administrativos com deficiência, transtorno global do desenvolvimento e altas habilidades no âmbito da UFG. As ações na inclusão de pessoas com deficiência se mostram necessárias, pois assim como destacado por Martins et al (2015), na Regional Jataí menos de 1% dos ingressantes apresentou algum tipo de deficiência.…”
Section: A B C D E F G Hunclassified